(untitled) (National Administration Journal, 2024)
In a highly competitive market, implementing an effective marketing strategy is essential to attract customers. The findings obtained during the second and third quarters of 2023 offer valuable results on the application of virtual coaching in neurolinguistic programming from the Marketing Department of the School of Management Sciences of the UNED. For this purpose, a qualitative research is proposed to determine its effectiveness as an Inbound Marketingstrategy from the virtual learning environment of the Marketing I subject. This tool, in addition to understanding the needs of students, is functional to improve their educational experience.